FACTORS ASSOCIATED WITH MENTAL SUFFERING IN PEOPLE WITH DIABETES MELLITUS DURING THE COVID-19 PANDEMIC - Ibiapina Costa Filho, Antonio Alberto; dos Santos Ribeiro, Laisa Maria; de Carvalho Alencar, Delmo; de Oliveira, Naila Albertina; Rabi, José Antonio; de Sousa Ibiapina, Aline Raquel (Cogitare Enfermagem, 2022)
Objective: to analyze the factors associated with mental distress in people with diabetes mellitus during the COVID-19 pandemic. Method: cross-sectional study, conducted in two Brazilian virtual communities of the Facebook platform, in the period from August 2020 to January 2021. The sample totaled 111 people with diabetes. The evaluation of health conditions was performed using an electronic form, and the Self Report Questionnaire-20 was used to identify mental suffering. Descriptive and inferential analyses were expressed by frequencies and simple and multiple logistic regression. Results: mental suffering is associated with being female, having a previous history of mental disorders (depression and anxiety), having been diagnosed with diabetes for more than six years, and the presence of ophthalmologic complications, which increase the chances of emotional instability. Conclusion: the study offers subsidies to the direction of support strategies that minimize the psychosocial impacts of the pandemic on people with diabetes.